Cari Mora - Harris, Thomas, 1940- (Grand Central Publishing, 2019)
"Twenty-five million dollars in cartel gold lies hidden beneath a mansion on the Miami Beach waterfront. Ruthless men have tracked it for years. Leading the pack is Hans-Peter Schneider. Driven by unspeakable appetites, he makes a living fleshing out the violent fantasies of other, richer men. Cari Mora, caretaker of the house, has escaped from the violence in her native country. She stays in Miami on a wobbly Temporary Protected Status, subject to the iron whim of ICE. She works at many jobs to survive. Beautiful, marked by war, Cari catches the eye of Hans-Peter as he closes in on the treasure. But Cari Mora has surprising skills, and her will to survive has been tested before. Monsters lurk in the crevices between male desire and female survival."--